Fruit and vegetable intake and incident and persistent poor sleep quality in a rural ageing population in South Africa: longitudinal study. Issue 5 (28th September 2022) - Pengpid, Supa; Peltzer, Karl
Abstract : Background: Fruit and vegetable intake may improve sleep. Aims: To assess the relationship between fruit and vegetable intake and sleep quality in a longitudinal study. Method: We analysed longitudinal data from two consecutive population surveys of adults in Agincourt, South Africa (2014–2015 and 2018–2019). Results: In total, 331 of 2975 participants without poor sleep quality in Wave 1 (11.1%) had incident poor sleep quality in Wave 2, and 270 of 3546 participants who had poor sleep quality in Wave 1 (7.6%) had poor sleep quality in both Waves 1 and 2 (persistent poor sleep quality). The prevalence of poor sleep quality at baseline was 17.2%. In the fully adjusted model for people without poor sleep quality at baseline, higher fruit and vegetable consumption (≥5 servings/day) was positively associated with incident poor sleep quality among men (AOR = 1.43, 95% CI 1.51–2.01) but not among women (AOR = 1.09, 95% CI 0.78–1.46). Two or more servings of fruits were positively associated with incident poor sleep quality among men (AOR = 3.35, 95% CI 1.96–5.72) and among women (AOR = 1.84, 95% CI 1.15–2.94). No models among men and women showed a significant association between vegetable intake and incident poor sleep quality or between fruit and vegetable intake, vegetable intake and persistent poor sleep quality. Fruit intake (one serving) was positively associated with persistent poor sleep quality among men (AOR = 1.76, 95% CI 1.00–3.08) but not among women (AOR = 1.42, 95% CI 0.93–2.18). Conclusions: Higher fruit and vegetable intake was independently associated with poorer sleep quality among men but not women, and higher fruit but not vegetable intake was associated with poorer sleep quality among both men and women.